2010
DOI: 10.1103/physrevlett.104.135002
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Measurable Ignition Criterion for Inertial Confinement Fusion

Abstract: A multidimensional measurable criterion for central ignition of inertial-confinement-fusion capsules is derived. The criterion accounts for the effects of implosion nonuniformities and depends on three measurable parameters: the neutron-averaged total areal density (rhoR(n)(tot)), the ion temperature (T(n)), and the yield over clean (YOC=ratio of the measured neutron yield to the predicted one-dimensional yield). The YOC measures the implosion uniformity. The criterion can be approximated by chi=(rhoR(n)(tot))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 16 publications
4
54
0
Order By: Relevance
“…Here we use the expression of Refs. [8,14,15] that is also related to the Livermore experimental ignition threshold factor (ITFx) [7,16,17]: where ρR is in g/cm 2 , the no-α neutron yield is in 10 16 , and the stagnating DT mass at bang time is in milligrams. The latter is often approximated with 1/2 of the unablated DT mass [8,15] …”
Section: The Higher Temperatures (Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we use the expression of Refs. [8,14,15] that is also related to the Livermore experimental ignition threshold factor (ITFx) [7,16,17]: where ρR is in g/cm 2 , the no-α neutron yield is in 10 16 , and the stagnating DT mass at bang time is in milligrams. The latter is often approximated with 1/2 of the unablated DT mass [8,15] …”
Section: The Higher Temperatures (Tmentioning
confidence: 99%
“…Based on analytic models and detailed numerical simulations [7,8], it was estimated that alpha-particle heating has led to a ∼2-2.5× enhancement of the fusion yield [6,8]. In the absence of alpha heating, the fusion yield from hydrodynamic compression alone would have been ∼ 4-5×10 15 . By extrapolating recent OMEGA results in size to match the 1.9 MJ of incident NIF laser energy, we find that the best-performing direct-drive OMEGA implosion to date would lead to a neutron yield of 4.5×10 16 neutrons and a level of alpha heating corresponding to about a 2× yield enhancement, similar to the indirect-drive HF targets at the same laser energy.…”
mentioning
confidence: 99%
“…In this letter, we consider yield amplifications ≤ 10 that are of most interest for current implosions on the NIF and characterstic of a subignited burning plasma. Using a simple model of the hot spot and shell dynamics (alpha heating model), we find the burning-plasma conditions for ICF and show that the fusion yield enhancement due to alpha heating depends only on the Lawson parameter [6,7] through a universal curve valid for direct and indirect drive ICF. It is shown that the alpha-heating model results agree with radiation-hydrodynamics simulations.…”
mentioning
confidence: 99%
“…Here I discuss a minimal model of ignition, simple enough for intuitive understanding, and its quantification by means of the partial derivatives (2). It is not meant to be a realistic description of the actual ignition of flammable gases or an inertial fusion capsule, although such capsules are a well-known and well-quantified example of a design problem with a steep cliff (Chang, et al 2010 Fig. 4).…”
Section: A Determinate Model: Ignitionmentioning
confidence: 99%
“…The first is the ignition of a flammable gas mixture by a small spark. This is a simple model of the more complex problem of ignition of a laser fusion capsule (Chang, et al 2010;Lindl, et al 2011;Haan, et al 2011;Edwards, et al 2011). The second is the well-known problem of plastic failure of a ductile material in tension (Ugural and Fenster 2011).…”
Section: Review Of Literaturementioning
confidence: 99%